Penghambatan Ekstrak Buah Mahkota Dewa (Phaleria macrocarpha) Terhadap Pertumbuhan Fusarium oxysporum f. sp. capsici Penyebab Layu Cabai Secara In Vitro - Adelin Elsina Tanati (Agrotek, 2012)
Fusarium oxysporum f.sp capsici is a fungi that causes wilt disease on chili plant. This pathogen is important because can decrease quality and quantity of crops. This research was carried out to know the inhibitation from the extract of Mahkota Dewa’s (Phaleria macrocarpha) fruit due to the gowth of F. oxysporum causal agent of withered disease on chili. In this research, use experimental method with RAL type. Treatment that be used are different volume from mahkota dewa’s fruit extract, i.e. P0 (0 ml); P1 (0.25 ml); P2 (0.5 ml); P3 (0.75 ml) and P4 (1.00 ml). Result shows that the extract of mahkota dewa’s fruit has tendency to inhibit the gowth of colony F. oxysporum through diameter of colony and spore density. The diameter average of colony on P0 is 3.45 cm and P4 is 2.86 cm. Standart measurment in density spore is spore ml-1 water. The highest density spore in P0 is 3.24 x 10; next on P1 is 2.43 x 107; P2 with 2.16 x 107; the average of P3 is 1.72 x 107; and P4 with the lowest density of spore is 1.29 x 107. Mahkota dewa’s fruit extract are more effected to density spore; and has potency as antifungi, because has compound bioactive are alkaloid, saponin and flavonoid.